2015
DOI: 10.18378/rvads.v10i1.3040
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de antagonismo de isolados de Trichoderma sp. contra o isolados de Fusarium sp., in vitro

Abstract: <p class="MsoNormal" style="margin-bottom: .0001pt; text-align: justify; line-height: 150%; mso-layout-grid-align: none; text-autospace: none;"><span style="font-size: 12pt; line-height: 150%; font-family: 'Times New Roman', serif;">Resumo </span><span style="font-size: 12.0pt; line-height: 150%; font-family: 'Times New Roman','serif';">– O uso discriminado de agrotóxicos acarreta em uma grande prejuízo a saúdes das pessoas e do meio ambiente. O uso de novos métodos de combate a pragas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…Trichoderma fungus is considered a free-living soil microorganism, which survives in tropical and temperate regions, being three species (T. harzianum, T. virens and T. viride) the most used in biological control of diseases and on growth promotion of several crops (Hoffmann et al, 2015). Many studies point out the use of Trichoderma to promote initial growth of many commercial crops, such as tomatoes and beans (Chacón et al, 2007;Guimarães et al, 2014), as well as an increase in grain yield and leaf crops (Azevedo Filho et al, 2011;Carvalho et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma fungus is considered a free-living soil microorganism, which survives in tropical and temperate regions, being three species (T. harzianum, T. virens and T. viride) the most used in biological control of diseases and on growth promotion of several crops (Hoffmann et al, 2015). Many studies point out the use of Trichoderma to promote initial growth of many commercial crops, such as tomatoes and beans (Chacón et al, 2007;Guimarães et al, 2014), as well as an increase in grain yield and leaf crops (Azevedo Filho et al, 2011;Carvalho et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Among these fungi, Fusarium oxysporum, Botrytis cinerea and Alternaria alternata are highlighted because they are very detrimental to the farmer's income because they attack a wide variety of plants [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…These values were higher than those found by Fantinel et al (2018), who evaluated the antagonistic potential of different isolates of Trichoderma and Baciulus thuringiensis against Colletotrichum siamense and found maximum MGIP of 32 % and 44.2 % on the 6 th and 12 th days, respectively. Hoffmann et al (2015) found that 3 of the 15 evaluated isolates had MGIP of 38.8 %, 44.4 %, and 48.9 % on the 7 th day of pairing, and 12 isolates showed high antagonistic potential, completely inhibiting the development of Fusarium sp., with growth inhibition percentages between 81.2 % and 94.4 %.…”
Section: Resultsmentioning
confidence: 93%